Órgão da Igreja de Nossa Senhora da Graça - Rui Paiva, Pedro Couto Soares, Hugo Sanches - Oliveira, Filipe (2012)
Este depósito consta de um excerto das notas redigidas para o CD intitulado Órgão da Igreja de Nossa Senhora da Graça, Tomar - Rui Paiva, Pedro Couto Soares, Hugo Sanches.